KULIAH KERJA MAHASISWA: PEMANFAATAN POTENSI BAMBU SEBAGAI KEMASAN RAMAH LINGKUNGAN PADA SEKTOR UMKM GUNA MENDORONG PEREKONOMIAN DI KELURAHAN CISARUA - Masripah, Ipah; Amelia, Lala; Nurhayati, Sheilla; Marina Salsyabila, Shelma; Solehah, Sopiana (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
Group IV Student Work Lecture (KKM) STIE Pasim Sukabumi 2023, research on Utilizing the Potential of Bamboo as Environmentally Friendly Packaging in the Micro, Small and Medium Enterprises (MSMEs) Sector to Boost the Economy in Cisarua Village, Babakan Jampang Village, RT.01, RW.11, Cikole District, Sukabumi City, West Java Province. The purpose of this study was to analyze how important it is to utilize the potential of bamboo as environmentally friendly packaging in the development strategy of Micro, Small and Medium Enterprises (MSMEs) to improve the economy of Cisarua Village. The research method used in the current research is qualitative, technically using general and comprehensive observation techniques, which means starting from interviews, and also direct observation. The results obtained from this research are that the community elevates local values ​​and synergizes with the surrounding environment, especially the use of bamboo as an environmentally friendly material.